Implementation of STEM-Integrated Modules and Wasaka Character Values to Improve Learning Outcomes - Muhsinah Annisa; Dasim Budimansyah; Mupid Hidayat; Atiek Winarti; Teguh Prasetio (Jurnal Penelitian Pendidikan IPA, 2024)
STEM education, which includes Science, Technology, Engineering and Mathematics, is essential to prepare students with the skills and knowledge required in the modern world. This study aims to evaluate the effectiveness of the implementation of a STEM-integrated module combined with Wasaka character values to enhance student learning outcomes. The Wasaka values, rooted in local culture, include religiousness, resilience, responsibility, and independence, and are integrated into the STEM curriculum to create a holistic educational approach. The research employs a quasi-experimental design with pre-test and post-test assessments 35 students in a field trial phase. Statistical analyses, including paired t-tests and Wilcoxon signed-rank tests, were used to determine the significance of differences in student performance before and after the intervention. The results show a significant improvement in student learning outcomes, with all students demonstrating higher scores in post-tests compared to pre-tests. The integration of STEM and Wasaka character values enhanced academic achievement. This research concludes that the STEM-integrated module with Wasaka values is effective in improving both cognitive and character aspects of students, providing a model for more comprehensive and culturally responsive educational practices.